A Legal Certainty of Dual Citizenship for Possession of Land - Cornelia Mella Vista (International Journal of Science and Society, 2022)
This research is to analyze and examine the legal certainty of children holding dual citizenship (bipatride) from mixed marriages to have property rights on land in Indonesia, as well as future arrangements to be able to provide equality for children holding dual citizenship to have property rights to land like other Indonesian citizens. The type of research used is normative juridical research, which means studying and analyzing formal legal rules, namely laws. Following the objectives to be achieved, this thesis research uses three approaches: the statutory approach, the conceptual approach, the historical approach, and the comparative approach. After the legal materials are collected, the legal issues are analyzed based on the collected legal materials. Based on the results of a review of existing legal materials, it is concluded that the legal certainty of dual citizenship holders (bipatride) owned by children from mixed marriages to have property rights on land is given similarities with foreigners as stipulated in Article 21 paragraph (4) of the UUPA which does not allow Indonesian citizens have dual citizenship (bipatride) to have property rights over land in Indonesia. Ownership rights are hereditary, strongest, and most complete rights that can be owned by people on land, keeping in mind the provisions in Article 6 of the UUPA can only be owned by Indonesian citizens who do not hold other citizenships such as dual citizenship owned by children from mixed marriages. Children holding dual citizenship (bipatride) can have ownership rights to land based on inheritance and only a time limit of 1 (one) year for them to be released to other people as stipulated in Article 21 paragraph (3) of the UUPA, which has been equated with provisions for foreigners.